Laws of nanosize molybdenum (VI) oxide layers optical properties change as a result of heat treatment; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 3 - Borisova N. V. (Chemistry, 2007)
Заглавие с титульного листа